Maytansinol Functionalization: Towards Useful Probes for Studying Microtubule Dynamics. Issue 5 (30th December 2022) - Boiarska, Zlata; Pérez‐Peña, Helena; Abel, Anne‐Catherine; Marzullo, Paola; Álvarez‐Bernad, Beatriz; Bonato, Francesca; Santini, Benedetta; Horvath, Dragos; Lucena‐Agell, Daniel; Vasile, Francesca; Sironi, Maurizio; Díaz, J. Fernando; et al.
Abstract: Maytansinoids are a successful class of natural and semisynthetic tubulin binders, known for their potent cytotoxic activity. Their wider application as cytotoxins and chemical probes to study tubulin dynamics has been held back by the complexity of natural product chemistry. Here we report the synthesis of long‐chain derivatives and maytansinoid conjugates. We confirmed that bulky substituents do not impact their high activity or the scaffold's binding mode. These encouraging results open new avenues for the design of new maytansine‐based probes. Abstract : The design and synthesis as well as biochemical and structural characterization of long‐chain maytansinoids and maytansinoid conjugates is reported. The results show the prospects of maytansinoids as probes to study microtubule dynamics and lead towards the design of new maytansine‐based derivatives.